Detecting the magnetic cosmic web through deep radio polarization imaging - Burnham-King, Lauren S (Department of Astronomy, 2018)
The polarisation of radio emission is one of the most powerful probes of magnetic fields in the cosmos. Faraday rotation of polarized radiation provides one of the methods to observe magnetic fields. Measuring the rotation of the polarisation angle of radiation from an extragalactic source over a broad radio bandwidth allows us to infer the properties of the magnetic fields that the radiation passed through on the path to the observer. In the last few decades, the presence of structure in the matter distribution of the universe has been observed. It remains an open question whether there are magnetic fields associated with this large-scale structure. Large-scale universe simulations allow us to investigate the effect of extragalactic magnetic fields on the spatial distribution of Rotation Measure (RM) of radio sources that will be detected in deep radio images with MeerKAT. We constructed lightcones out to z = 1 from large-scale universe simulations as a base for our model and assemble a routine to trace large scale structures, attach magnetic fields to the structure and construct RM observations. The aim is to explore whether deep MeerKAT continuum observations will be able to detect magnetic fields associated with large-scale structure (the so-called magnetic cosmic web).